SILENT EXODUS DALAM GEREJA: KAJIAN TEOLOGIS TERHADAP FENOMENA JEMAAT YANG MASIH BERIBADAH TETAPI KEHILANGAN KETERIKATAN EKLESIAL - Kristia Mesaarruan; Daniel Sampe Ruru; Irvan Yoga; Yuyun; Feby Febryanti (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
The phenomenon of silent exodus emerges when congregants continue to participate in worship—whether physically or virtually yet undergo a degradation of communal attachment and spiritual commitment. This study analyzes the phenomenon from a theological-ecclesiological perspective using a qualitative-descriptive approach based on library research,. Data analysis employs the Miles & Huberman technique, which involves data reduction, data display, and verification through content analysis,. The research findings identify several key contributing factors: individualism, consumerism, digitalization, church leadership crises, and the cultural shifts of the younger generation. From an ecclesiological standpoint, the church is ideally the "body of Christ" in fellowship, as described in Ephesians 2:19–22 and 1 Corinthians 12:12–27. Silent exodus is viewed as a crisis of belonging that aligns with Grace Davie’s concept of “believing without belonging”. Such conditions require the church to revitalize its calling for koinonia (fellowship) through inclusive pastoral care and an adaptive church model (such as the elastic church) that synergizes physical and digital spaces. Through the Spiral Silent Exodus conceptual diagram, this study concludes the urgency of addressing these ecclesial challenges and recommends further field research within the Indonesian church context.